1992
DOI: 10.7557/2.12.3.1044
|View full text |Cite
|
Sign up to set email alerts
|

A serological, retrospective study in reindeer on five different viruses

Abstract: Serological investigations on different cervidae have indicated the presence of several viruses common in domestic ruminants (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…The high seroprevalence for alphaherpesvirus and pestivirus in all herds (with the exception of KA and AK) is in accord with most previous serological surveys for these viruses in Rangifer worldwide [49,68,75,[84][85][86][87][88][89][90]. Although the assays used in this study detected antibodies reacting against antigens of bovine viral diarrhea virus (BVDV) and bovine herpesvirus type 1 (BHV-1), they also cross-react with antibodies to cervid-specific viruses [91,92].…”
Section: Alphaherpesvirus and Pestivirussupporting
confidence: 88%
“…The high seroprevalence for alphaherpesvirus and pestivirus in all herds (with the exception of KA and AK) is in accord with most previous serological surveys for these viruses in Rangifer worldwide [49,68,75,[84][85][86][87][88][89][90]. Although the assays used in this study detected antibodies reacting against antigens of bovine viral diarrhea virus (BVDV) and bovine herpesvirus type 1 (BHV-1), they also cross-react with antibodies to cervid-specific viruses [91,92].…”
Section: Alphaherpesvirus and Pestivirussupporting
confidence: 88%
“…In a previous serological investigation of reindeer in Finnmark, neutralizing pestivirus antibodies were detected in animals from 6 of 7 investigated herding districts, with a total seroprevalence of 17% (Stuen et al, 1993). Pestivirus antibodies have also been detected in reindeer in Finland (58%; Neuvonen et al, 1983) and Sweden (6%; Rehbinder et al, 1992), and in caribou (R. tarandus) in Canada (60%; Elazhary et al, 1979) and Alaska (3%; Zarnke, 1983).…”
Section: Introductionmentioning
confidence: 89%
“…Alphaherpesviruses serologically related to bovine herpesvirus 1 (BoHV1) have been detected in a wide range of wildlife species and are also widely distributed in populations of semidomesticated reindeer in Norway (7,34), Sweden (24,27), and Finland (11), as well as in reindeer and caribou populations in North America (12). Recent viral characterization of isolates from Norway has shown that cervid herpesvirus 2 (CvHV2) is the alphaherpesvirus circulating in the reindeer populations (7).…”
mentioning
confidence: 99%